Terrors of the night : Canadian accounts of eerie events and weird experiences - Colombo, John Robert, 1936- (Toronto ; : Tonawanda, NY : Dundurn Group, 2005)
De "vreemde gebeurtenissen" waar Colombo over schrijft zijn wel heel uiteenlopend: hekserij, uitzonderlijke weersomstandigheden, wilde dieren, wonderlijke genezingen, ...
Includes bibliographical references.
Keywords: Parapsychology -- Canada